UV laser sterilization of Bacillus atrophaeus spores on ceramic tiles. Issue 1 (1st January 2022) - Jang, Hanbyeol; Nguyen, My-Chi; Noh, Sojung; Cho, Woo Kyung; Sohn, Youngku; Yee, Kiju; Jung, Heesoo; Kim, Jeongkwon
Abstract: Ultraviolet (UV) radiation is one of the most common methods for sterilizing materials with suspected biological warfare agent contamination. In this study, UV laser sterilization of ceramic tiles was investigated as a method for destroying Bacillus atrophaeus spores. The effects of UV irradiation were evaluated as a function of water absorption (porous and vitrified), tile color (black and white), and surface brightness (matte and glossy). Spores were loaded onto the surface of each tile and irradiated with a 266-nm UV laser. The irradiated spores were then removed by scraping with a razor blade and cultured in an agar plate for 24 h. The sterilizing effects of the UV laser were greater on the vitrified (group BIb ) tiles than on the porous (group BIII) tiles. In addition, sterilization was more effective on white and matte tiles than on black and glossy tiles, respectively.